Critical code studies - Marino, Mark C. (Software studies (Cambridge, Mass.), 2020)
"Critical Code Studies (CCS) names a set of methodologies for the exploration of computer source code using the hermeneutics of the humanities. Like 10 PRINT CHR$ (205.5 + RND (1)); : GOTO 10, Mark Marino's Critical Code Studies treats code not as merely functional but as a text, one that can be read, and misinterpreted, by non-programmers. As the author notes, code's "meaning is not determined entirely by the programmer's intention but also by how it is received and recirculated. That is not to argue that code can be taken out of context or that code means whatever people say it means but rather that the meaning of code is contingent and that code is subject to the rhetorical triad of speaker, audience (both human and machine), and message." It is time to develop methods of tracing the meaning of code. Computer source code has become part of our political, legal, aesthetic, and popular discourse. Code is being read by lawyers, corporate managers, artists, pundits, reporters, and even literary scholars. Code is being used in political debate, in artistic exhibitions, in popular entertainment, and in historical accounts. As code reaches more and more readers and as programming languages and methods continue to evolve, we need to develop methods to account for the way code accrues meaning and how the readers and shifting contexts shape that meaning. We need to learn not only to understand the functioning of code but the way code signifies. We need to learn to read code critically. Critical Code Studies offers a CCS "starting kit," a set of techniques that scholars and other interested parties can use to interpret code in a non-computational context"--